2011
DOI: 10.1177/229255031101900307
|View full text |Cite
|
Sign up to set email alerts
|

Improving Journal Clubs Through the Use of Positive Deviance: A Mixed-Methods Study

Abstract: Using the principles of positive deviance, journal club satisfaction was improved. The interventions presented could be used to improve journal clubs at other institutions. In addition, the principles of positive deviance can be used to address a variety of administrative and educational challenges faced by plastic surgery programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…20 30–32 42 45 54 Conceptualisations of the approach also varied. Community involvement was central to Anzarut et al 's definition, 28 while Kennedy et al 33 emphasised that determinants of success do not necessarily oppose determinants of failure. Positive deviance was commonly used as a single improvement method, but 26 articles did not explicitly state which process had been followed (see online supplementary file 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 30–32 42 45 54 Conceptualisations of the approach also varied. Community involvement was central to Anzarut et al 's definition, 28 while Kennedy et al 33 emphasised that determinants of success do not necessarily oppose determinants of failure. Positive deviance was commonly used as a single improvement method, but 26 articles did not explicitly state which process had been followed (see online supplementary file 4).…”
Section: Resultsmentioning
confidence: 99%
“…Stage 2 was conducted using quantitative, routinely collected data and/or surveys in four projects. 22 23 28 33 Mixed methods were used in four additional projects, typically combining interviews, focus groups or DADs with surveys and routinely collected data. 11 21 35 37–39 Twelve projects included comparison groups to assess how positive deviants differed from others (see online supplementary file 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 35 One study found that faculty mentorship for article selection significantly improved participant satisfaction. 38 Alternatively, faculty may select the articles for inclusion. This technique offers the advantage of ensuring high-quality article selection, while allowing the learners to focus on analyzing and applying the selected articles.…”
Section: Introductionmentioning
confidence: 99%
“… 1 – 3 However, many challenges are encountered when designing an effective journal club structure that actively engages learners and accomplishes these objectives. 4 , 5 , 6 Most programs assign designated residents to deliver an oral presentation, 7 while the remainder of the participants have little motivation to prepare beforehand and risk becoming passive listeners. The traditional Socratic method of “calling on” residents may encourage participation, but may also conflict with the desire to create a collegial atmosphere.…”
Section: Introductionmentioning
confidence: 99%